Asbestos: current issues related to cancer and to uses in developing countries - Algranti Eduardo (Cadernos de Saúde Pública, 1998)
Asbestos is one of the main occupational carcinogens recognized and studied in the literature. Its uses have undergone major changes in recent decades, with severe restrictions on commercial amphiboles according to different patterns: in developed countries asbestos is strictly controlled or banned, except in Japan, while in developing countries consumption has leveled off or increased. As an example, Brazil is one the seven world leaders in asbestos production and consumption. Although there is a clear excess of mesotheliomas linked to amphibole exposure, mainly to crocidolite, there is no evidences that chrysotile is harmless to the pleura. Also, the relationship between fibrogenesis and carcinogenesis is not sufficiently understood to defend the concept that there are protective exposure limits to both diseases. "Controlled use" policy may be effective at the occupational level in a select group of companies, representing only a fraction of the exposed population. In developing countries subject to economic pressures, these issues merit proper discussion to avoid unnecessary disease and death.